Adrenal suppression following intralesional corticosteroids for periocular haemangiomas. Issue 6 (14th February 2011) - Morkane, C; Gregory, J W; Watts, P; Warner, J T
Abstract : Background/aims: Treatment with intralesional triamcinolone/betamethasone is recommended for infantile sight-threatening periocular haemangiomas. This study investigates the endocrine and weight changes in 15 infants undergoing therapy over 12 years. Methods: 15 infants, median age 19 weeks (range 10–56) receiving intra/perilesional triamcinolone/betamethasone underwent serial measurement of weight, early morning serum cortisol and adrenocorticotropic hormone (ACTH) before and after injection. Results: Cortisol fell from a median (range) of 383 (112–594) to 28 (<10–506) nmol/l (p=0.005) and ACTH from 26 (14–134) to 9 (5–20) ng/l (p=0.05) from before injection to 4 weeks after treatment. Prolonged adrenal suppression occurred in 13 out of 15 cases with time to recovery being 19.5 (4–65) weeks. Failure to gain weight appropriately was observed in 14 infants but recovered once normal adrenal function was re-established. Conclusion: Prolonged adrenal suppression following triamcinolone/betamethasone injection for periocular haemangiomas is common and associated with faltering weight gain.